IMPROVING THE KNOWLEDGE OF STUDENTS OF STATE SENIOR HIGH SCHOOL 18 MEDAN CLASS X REGARDING EARTHQUAKE DISASTERS THROUGH NEWS VIDEO MEDIA - Susilawati, Susilawati; Fareby, Tazla Nia; Wahyuni, Nabila; Laspita, Herlia Nur; Pratiwi, Afrida Dina (HEARTY, 2026)
This study aims to determine the effectiveness of using news video media in increasing the knowledge of grade X students of SMA Negeri 18 Medan regarding earthquake disasters. Earthquakes are disasters that have a significant impact on people's lives, especially in earthquake-prone areas. News video media was chosen because of its ability to present factual information visually and attractively. The methods used included observation, interviews, and pretest-posttest questionnaires on 36 students. The results showed a significant increase in knowledge after the news video media intervention, with an average pretest score of 8.53 to 9.81 in the posttest (p = 0.000). This media is effective as an educational tool that strengthens earthquake disaster preparedness.